Spinal Brucellosis: A Very Subtle Cause - Soumil Singhal (Asian Journal of Medical Radiological Research, 2018)
Osteoarticular brucellosis is a serious complication of human brucellosis. Brucellosis of the spine is not a very common cause of back pain in an Indian population. I present here a case presenting with an unusual backache diagnosed to finally have brucellosis and its clinical presentation and imaging findings.